2004
DOI: 10.1525/mp.2004.22.2.297
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Large-Scale Form on Continuous Ratings in Response to a Contemporary Piece in a Live Concert Setting

Abstract: Listeners responded continuously at the world and North American premiere concerts of The Angel of Death by Roger Reynolds using one of two rating scales: familiarity or resemblance of musical materials within the piece and emotional force. Two versions of the piece were tested in each concert in different presentation orders. Functional data analysis revealed the influence of large-scale musical form and context on recognition processes and emotional reactions during ongoing listening. The instantaneous resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…By contrast, the segmentation task and the arousal judgment revealed that participants actually perceived the similar organization of original and counterpart. This finding suggests that participants may be sensitive to large-scale structures in music (both tonal and atonal) even though they are not able to detect explicitly when this structure was manipulated (see McAdams et al, 2004, and, for convergent findings). Interestingly, music training was not found to modulate the listeners' sensitivity to large-scale structures, which is consistent with data reported by Bigand and Poulin-Charronnat (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the segmentation task and the arousal judgment revealed that participants actually perceived the similar organization of original and counterpart. This finding suggests that participants may be sensitive to large-scale structures in music (both tonal and atonal) even though they are not able to detect explicitly when this structure was manipulated (see McAdams et al, 2004, and, for convergent findings). Interestingly, music training was not found to modulate the listeners' sensitivity to large-scale structures, which is consistent with data reported by Bigand and Poulin-Charronnat (2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, listeners encountered difficulties when they were asked to perform more abstract tasks such as judgment of belongingness. In a study carried out at the premier concerts of The Angel of Death (McAdams, Vines, Vieillard, Smith, & Reynolds, 2004), listeners continuously rated one of two dimensions: familiarity (resemblance of musical material within the piece) or emotional force. The study revealed the influence of large-scale musical form and context on recognition processes and listener's emotional reactions.…”
Section: Cognitive Psychology Perspectivementioning
confidence: 99%
“…Eight collections of continuous responses were gathered as part of an intricate experiment involving two premier concerts on different continents, each presenting two versions of Roger Reynolds' The Angel of Death, a 35-minute piece for piano, orchestra, and computerprocessed sound (McAdams, Vines, Vieillard, Smith & Reynolds, 2004). The first concert was presented in 2001 at the Grande Salle of the Centre Georges Pompidou in Paris, France with the Ensemble Court Circuit, the other at the Mandeville Auditorium of the University of California, San Diego in La Jolla, California in 2002 with the Sonor Ensemble.…”
Section: The Angel Of Death Projectmentioning
confidence: 99%
“…This question has attracted research with a focus on acoustic/perceptual features that include: sound intensity/loudness (Chapin, Large, Jantzen, Kelso, & Steinberg, 2008;Olsen, Stevens, & Tardieu, 2007); frequency/pitch and tonality (Kessler, Hansen, & Shepard, 1984;Windsor, 1997); sound duration/meter and tempo (Boltz, 1998;Chapin, et al, 2008;Quinn & Watt, 2006;Todd, Cousins, & Lee, 2007;Vuust, Ostergaard, Pallesen, Bailey, & Roepstorff, 2009); and spectrum/timbre (Bailes & Dean, 2007;Caclin, McAdams, Smith, & Winsberg, 2005;Gordon & Grey, 1978), as these relate to perceived structure and emotional response (Bailes & Dean, 2009;Bigand, Vieillard, Madurell, Marozeau, & Dacquet, 2005;Dubnov, McAdams, & Reynolds, 2006;Gabrielsson & Lindstrom, 2001;Leman, Vermeulen, De Voogdt, Moelants, & Lesaffre, 2005;Schubert, 2004;Sloboda, 1991;Sloboda & Lehmann, 2001). An issue in this work is the inadequacy of treating music as a static entity, since perception is determined by the temporal organization of these acoustic properties (Brittin & Duke, 1997;Deliège, Mélen, Stammers, & Cross, 1996;Krumhansl & Kessler, 1982;Lalitte & Bigand, 2006;McAdams, Vines, Vieillard, Smith, & Reynolds, 2004;Schubert, 2004;Sloboda & Lehmann, 2001). This paper will detail an analytical method allowing for just such a dynamic examination of the relationship between acoustical properties of a composition with real-time listener perceptions of its structure and its affective content.…”
Section: Abstract: Perception Affect Acoustics Autoregressive Timementioning
confidence: 99%